If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-7(1x-1)=10
We move all terms to the left:
2x-7(1x-1)-(10)=0
We add all the numbers together, and all the variables
2x-7(x-1)-10=0
We multiply parentheses
2x-7x+7-10=0
We add all the numbers together, and all the variables
-5x-3=0
We move all terms containing x to the left, all other terms to the right
-5x=3
x=3/-5
x=-3/5
| -6x+19(-x+2)=12 | | -48x=-7x^2=64 | | x=+20180 | | P=10x-(60-4x) | | 0.25x=-0.3 | | x+2+2x=+12 | | X+4+2x=+20 | | 4^(x+35)=64^(x-3) | | 2x-24=-30-x | | 0.6x-0.66x=3 | | J+j+j=77 | | J+j+j-3=77 | | J-3+j+j=77 | | 0.2x=0.34335 | | 1x+1x+1x=3 | | 0=(p^2+6p-16) | | 0=(-p^2+6p-16) | | 0.2x=0.035 | | 0=-p^2+6p-16) | | 8x+(-12)=-4 | | 10x–7=6x–1 | | M²-3m+2=0 | | 8x+(-12)=4 | | 0=(a^2-11a+28) | | -6x-4=4 | | -8x-6=4 | | 4(5)^(2x-1)=500 | | 20x=3.5 | | 6.4=(-0.4r | | x^2+60x-40=900 | | 36^(2x-3)=6 | | 25x=-0.3 |